Selective modification of oleuropein, a multifunctional bioactive natural product - Amel Jerbi; Paul Mosset; René Grée; Majed Kammoun (Journal of Saudi Chemical Society)
Oleuropein is the major phenolic compound extracted from olive leaves and it is also present in olive fruits and virgin olive oil. It has already demonstrated a wide range of pharmacological activities, but new derivatives have to be designed in order to obtain useful Structure–Activity Relationships for this family of products, as well as new analogs with improved and/or different biological properties. However, taking into account the multiple OH groups (catechol and sugar) present in oleuropein, the selective modification of this natural product is a challenging problem. In this paper, we present an efficient strategy allowing the selective modification at the primary alcohol position of this natural product. Using appropriate protection/deprotection sequences, we prepared by hemisynthesis several triazoles linked to the oleuropein core, as representative examples for the development of such an approach. Keywords: Oleuropein, Debenzylation, Benzyl protecting group, Hemisynthesis, Triazole, Click chemistry